2014 16th European Conference on Power Electronics and Applications 2014
DOI: 10.1109/epe.2014.6910734
|View full text |Cite
|
Sign up to set email alerts
|

Analytical determination of the first resonant frequency of differential mode chokes by detailed analysis of parasitic capacitances

Abstract: AcknowledgmentsThe authors would like to thank ABB Switzerland corporate research center in Baden/Daettwill for initiating and supporting this work. AbstractIn this paper the important parasitic capacitances of chokes are analyzed and defined. This work contributes to a general understanding of capacitive coupling in wound elements. Based on calculations from previous studies a more precise, wide range algorithm is proposed to calculate these parasitic capacitances of toroidal chokes. With these results a meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Nevertheless it is generally not accurate enough for loose winding made with round conductors. In the literature this problem is solved with image theory [18], equivalent segment or arc parasitic capacitances [19]- [22], a combination of the two previous methods [23], conformal transform [24], or 2D FEM [25], [26]. The latter approach will be used in this paper because it takes into account insulation layers, coating, inter-turn and turn-core spaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless it is generally not accurate enough for loose winding made with round conductors. In the literature this problem is solved with image theory [18], equivalent segment or arc parasitic capacitances [19]- [22], a combination of the two previous methods [23], conformal transform [24], or 2D FEM [25], [26]. The latter approach will be used in this paper because it takes into account insulation layers, coating, inter-turn and turn-core spaces.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the modelling of the EPC, some articles propose ways to reduce it. The authors of [23] have identified the turn-core capacitance as the most important one in the total EPC, and its dependence with the inter-turns space. Therefore they suggest to keep the winding tight to avoid the increase of the parasitic capacitive coupling between turns and core, and thus to reduce the EPC, (this has been confirmed in [18], [25], [26]).…”
Section: Introductionmentioning
confidence: 99%
“…For single-layer windings on high-permittivity materials, the coupling C tc could also be a dominant effect over C tt in determining the total electrical coupling between windings [13], [14]. Since C tc tends to increase for loose windings [10], this winding strategy increases the EPC of inductors with high-permittivity cores [14]. However, the situation is different if the core material does not have such a high permittivity, as is the case with NiZn ferrites [13].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the problem posed by parasitic capacitances in inductive filtering components, various works in the literature focus on estimating the equivalent parasitic capacitance (EPC) for inductors or for specific connections of a CMC [5], [8], [9], [10], [11]. These studies demonstrate that EPC generally has a contribution arising from the electrical coupling between turns of the inductor and another contribution associated with the coupling of turns to the core.…”
mentioning
confidence: 99%
“…2 with a highself-resonant frequency. However, core geometries are restricted ( [16], [17]) and windings costs may be increased. Alternatively, a second choke may be added in series with that in Fig.…”
Section: B Spectra Of 2 Voltage and Switching Lossmentioning
confidence: 99%